Originally βíος. Biolaw Historical Roots - Alibrandi, Rosamaria (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2014)
The human rights which are on the foundations of the birth of bioethics are related to the topics concerning the human body we are born with, which has to be ruled by law and which must subsequently make the origin of the necessary look onto biopolitics. Human body made privileged land for medical power and an interaction in between biopolitics, medicalisation and biopower arose. However, the law is becoming more and more a stepped network which welcomes other factors than the established legal meanings, namely those external and informal factors which are halfway in between social praxis (the space outside the margins of the law we could possibly define as flexible law). What kind of pressure and to what extend do people and public opinion apply on the daily password laws they have to overcome?